2006
DOI: 10.1108/14777830610702520
|View full text |Cite
|
Sign up to set email alerts
|

Addressing sustainability early in the urban design process

Abstract: Purpose -Designers and planners in the UK are being asked by government to address sustainability. This paper seeks to explore how such issues can be addressed with the urban design process. From the literature, it is unclear when specific sustainability issues should be addressed, who actually makes decisions and what influences them, or how different stakeholders are engaged. Design/methodology/approach -A case study is presented, focusing on the early stages of an urban design and redevelopment process taki… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
24
0
10

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 64 publications
(34 citation statements)
references
References 19 publications
0
24
0
10
Order By: Relevance
“…The existence of more than 70 different definitions for sustainability (Holmberg and Sandbrook, 1992) highlighted its importance and illustrated the efforts made by different academic and practical disciplines to define and understand its implications to their fields. However, all definitions agree that it is of prime importance to consider the future of the planet and develop innovative ways to protect and enhance the Earth while satisfying various stakeholders' needs (Boyko et al, 2006). Scientific evidence showed that humanity is living unsustainably.…”
Section: Sustainabilitymentioning
confidence: 99%
“…The existence of more than 70 different definitions for sustainability (Holmberg and Sandbrook, 1992) highlighted its importance and illustrated the efforts made by different academic and practical disciplines to define and understand its implications to their fields. However, all definitions agree that it is of prime importance to consider the future of the planet and develop innovative ways to protect and enhance the Earth while satisfying various stakeholders' needs (Boyko et al, 2006). Scientific evidence showed that humanity is living unsustainably.…”
Section: Sustainabilitymentioning
confidence: 99%
“…Trata-se, ao contrário, de (Boyko et al, 2006;Nam & Pardo, 2011a;Toppeta, 2010;Rasoolimanesh et al, 2011).…”
Section: As Cidades Do Futuro: Cidades Inteligentesunclassified
“…Tais desafios, decorrentes da pressão por efetividade no atendimento às demandas sociais, exigem novas abordagens para seu planejamento, projeto, financiamento, execução e operação (Boyko et al, 2006;Harrison & Donnelly, 2011;Rasoolimanesh et al, 2011). O cenário torna-se mais desafiador quando consideradas as restrições de natureza legal-institucional e econômica para a destinação de recursos públicos e a competição cada vez mais agressiva entre as cidades para a atração de investimentos, visto que as receitas dos governos geralmente chegam mais tarde do que as demandas ou são equivocadamente destinadas (Nam & Pardo, 2011a;Cadena et al, 2012).…”
Section: Introductionunclassified
“…O relacionamento sólido entre academia-empresa-governo pode contribuir para a criação de novos nós nas redes de inovação urbana, capazes de estimular, gerar, promover e catalisar as Nesse sentido, "(...) é chegado o tempo de mostrar como as cidades inovadoras e a inovação nas cidades podem fazer frente aos desafios da sustentabilidade, à criação e distribuição de riquezas, aos investimentos necessários em infraestrutura, reduzindo a pobreza e funcionando de forma eficaz e eficiente em benefícios de todos" (MARCEAU, 2008, p. 145, tradução nossa). O cenário do crescimento urbano faz com que as cidades busquem alternativas e coloque esforços no fomento à criatividade e na inovação, de forma a que sejam lançadas as bases para uma nova ordem urbana (BOYKO et al, 2006;SCOTT, 2006;JOHNSON, 2008;BARNES, 2010). Nessa altura, é relevante afirmar que a inovação não está restrita às empresas, assim como ciência e tecnologia não estão circunscritas aos ambientes acadêmicos.…”
Section: Introductionunclassified